(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article presents ideas for designing a modern mechatronic module that allows the treatment and reuse of technical water in industrial enterprises, thus contributing to more efficient resource management. Today, as the scope of technical water usage in industrial sectors continues to increase, saving water resources through its reuse is becoming crucial. The proposed device ensures the step-by-step purification of large and small pollutants in technical water and brings it to a state suitable for reuse. The components of this module include filtration stages, a pumping system, automated sensors, a control unit, and monitoring modules. The device’s operation is automatically controlled, and real-time monitoring is carried out. This system plays an important role in ensuring environmental safety in industrial enterprises, reducing costs, implementing sustainable production principles, and improving water use efficiency. Additionally, it helps in meeting regulatory environmental standards by effectively reducing water pollution.